Restorative Justice sebagai Alternatif Penyelesaian Kasus Pemeliharaan Landak Langka di Bali - Ahnaf Nur Fauzan Romadhon; Enjang Rohiman; Ai Nazwa Nurbayanti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The concept of restorative justice is being explored as an alternative approach to resolving conservation violations caused by ignorance, as demonstrated in the I Nyoman Sukena case in Indonesia. This research aims to examine the potential of restorative justice to deal with such cases more humanely and effectively. A normative juridical method was used, focusing on legal regulations and case analysis relating to wildlife conservation. The results show that restorative justice, which emphasizes dialogue and education, can prevent recurrence and foster public awareness of protected species without imposing strict criminal sanctions. This approach, which is in line with Indonesian values, can reduce the burden on the judiciary and support conservation goals.